53.5k views
0 votes
−30=5(x+1) please simplify this for khan academy. org

User Josh Earl
by
5.9k points

2 Answers

6 votes

Answer: x=-7

Explanation:

-30=5(x+1)

multiply the brackets

-30=5x+5

take away 5x from both sides of the equation

-30-5x=5

add 30 to both sides

-5x=35

divide both sides by -5

x=-7

User Philipp Johannis
by
5.2k points
5 votes

Answer:

-7 =x

Explanation:

−30=5(x+1)

Divide each side by 5

−30/5=5/5 (x+1)

-6 = x+1

Subtract 1 from each side

-6-1 = x+1-1

-7 =x

User Thegeko
by
5.5k points